Family Involvement and Agency Cost Control Mechanisms in Family Small and Medium‐Sized Enterprises. (29th December 2013) - Songini, Lucrezia; Gnan, Luca; Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan
<x xml:space="preserve">Abstract</x> Family firms may experience different agency conflicts to the classical principal‐agent conflict, which arise depending on the varying extent of family involvement. Agency cost control mechanisms should be introduced to cope with them. The paper focuses on family involvement, in governance (FIG) and in management (FIM), agency cost control mechanisms, and financial performance in family SMEs. The results show that FIG is negatively related to agency cost control mechanisms, but they are positively related to FIM, Finally, the importance of agency cost control mechanisms positively influences the financial performance. Hypotheses were tested using LISREL.